Tandem Conversion of CO2 to Valuable Hydrocarbons in Highly Concentrated Potassium Iron Catalysts. Issue 12 (15th May 2019) - Ramirez, Adrian; Ould‐Chikh, Samy; Gevers, Lieven; Chowdhury, Abhishek Dutta; Abou‐Hamad, Edy; Aguilar‐Tapia, Antonio; Hazemann, Jean‐Louis; Wehbe, Nimer; Al Abdulghani, Abdullah J.; Kozlov, Sergey M.; Cavallo, Luigi; Gascon, Jorge
Abstract: The alarming atmospheric concentration and continuous emissions of carbon dioxide (CO2 ) require immediate action. As a result of advances in CO2 capture and sequestration technologies (generally involving point sources such as energy generation plants), large amounts of pure CO2 will soon be available. In addition to geological storage and other applications of the captured CO2, the development of technologies able to convert this carbon feedstock into commodity chemicals may pave the way towards a more sustainable economy. Here, we present a novel multifunctional catalyst consisting of Fe2 O3 encapsulated in K2 CO3 that can transform CO2 into olefins via a tandem mechanism. In contrast to traditional systems in Fischer‐Tropsch reactions, we demonstrate that when dealing with CO2 conversion (in contrast to CO), very high K loadings are key to activate CO2 via the well‐known 'potassium carbonate mechanism'. The proposed catalytic process is demonstrated to be as productive as existing commercial processes based on synthesis gas while relying on economically and environmentally advantageous CO2 feedstock. Abstract : Potassium carbonate‐iron catalyst for tandem conversion of CO2 : The potassium carbonate activates the CO2 while undergoing several transformation, yielding KOOCH and releasing CO. This CO is subsequently hydrogenated to olefins on the iron nanoparticles via Fisher‐Tropsch.